CT predicts intraprocedural hemodynamics with computational fluid dynamics in TMVR-ineligible patients undergoing M-TEER - Kirchner, Johannes; Gerçek, Muhammed; Omran, Hazem; Kassar, Mohammad; Gräni, Christoph; Praz, Fabien; Rudolph, Felix; Rudolph, Volker; Rudolph, Tanja K. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHemodynamic outcomes in patients undergoing transcatheter mitral edge-to-edge repair (M-TEER) are difficult to predict. Computational fluid dynamics (CFD) is frequently used in biomedical engineering to simulate blood flow patterns under various conditions.ObjectivesWe developed a standardized workflow for individualized CFD analyses to predict postinterventional mitral valve gradients and residual regurgitation following TEER.MethodsTwenty patients with severe mitral regurgitation (MR) from two high-volume centers underwent full-cycle cardiac computed tomography before intervention. Based on the specific valve morphology, individualized CFD simulations were performed to calculate MR volumes prior to intervention and estimate hemodynamics after M-TEER.ResultsCFD analyses (mean age 80 ± 4 years, 55% male) showed excellent correlation between baseline proximal isovelocity surface area (PISA)-based MR volumes, median 40 ml [interquartile range (IQR): 30–49 ml], and CFD-based calculation, median 30 ml (IQR: 27–54 ml; R = 0.917; P < 0.001), as well as between baseline effective regurgitant orifice area (EROA) assessed in transesophageal echocardiography (TEE) and CFD-measured EROA (R = 0.869; P < 0.001). After device implantation, the correlation between intraprocedural TEE-measured and CFD-estimated residual MR (R = 0.949; P < 0.001) and EROA (R = 0.841; P < 0.001) remained robust. Median postinterventional diastolic pressure gradient (TEE) was 2.8 mmHg (IQR: 1.7–4.0), which closely correlated with the CFD-estimated gradient of 1.4 mmHg (IQR: 2.3–4.5, R = 0.905; P < 0.001).ConclusionsThis is the first study to use a standardized CFD workflow for MR evaluation in patients undergoing TEER. In the future, CFD-based analyses may serve as a key diagnostic tool for procedural planning of TEER.